Quel devenir pour l’Etat, la nation, l’Etat-nation dans la Bolivie d’Evo Morales ? - Christine Delfour (Les Cahiers ALHIM)
The making of the State, the Nation and the Nation-State in Bolivia has been an endless quest since the foundation of the Republic in 1825. However there are two stages of significant importance: the first one, during the 50’s, when the National Revolutionary Movement (MNR) allows the transition from modernization to modernity with the universal suffrage, the agrarian reform and several nationalizations without recognizing the radical otherness of the Indian; the second stage, during the 90’s, when the successive governments vote a «pluriethnical» Constitution as well as laws of popular participation. This process comes to a climax with the election of the Indian President Evo Morales in December 2005. Among issues discussed in this paper: How can we define national identity–ies? What is the significance of the «pluri-multi» concept? What do we mean by «ethnical availability»? What is the impact of the «rebellious cycle»? What new patterns of economic development? What alternative models of territorial organization? What relationship between social movements, political parties and the State? How can avoid the threat of bipolarization?